Vidsubstantyvni adverbiatives in form of aninstrumental case in Ukrainian dialects (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
Dialectal vidimennykovi adverbs in the different grammaticalforms (masculine, woman, middle masculine, in he form of greatnumber) of an instrumental case formed as a result of thesynthetic (case) and analytical (prepositionalcase) passingof substantivesinto adverbiatives are analysed in the article.
Keywords: adverb; instrumental case; adverbiative; аdverbialization; dialect